Graphene-based nanocarbons for catalytic degradation of aqueous contaminants - Indrawirawan, Stacey (Curtin University, 2016)
This study focuses on catalytic oxidation of organic pollutants, phenol and nitrobenzene (NB), in wastewater. Various carbons were used for adsorption and catalytic activation of peroxymonosulfate (PMS) and persulfate (PDS) for phenol and NB degradation. It was observed that free radicals, hydroxyl (•OH) and sulfate (SO4•–) radicals, were generated in catalytic activation of PMS and PDS and reaction temperature, aqueous pH and catalyst properties played significant roles in catalytic oxidation.